Environmentally friendly sealing UV adhesive and preparation method thereof

Through the combination of modified acrylate, epoxy resin and reinforcement filler, combined with the ultraviolet curing technology of photoinitiator, the problem of poor high-temperature resistance and performance of UV sealants at high temperatures is solved, and good mechanical properties and sealing performance are achieved in high temperature environments.

CN118813143BActive Publication Date: 2025-05-09BONDWAY (DONGGUAN) ELECTRONIC MATERIALS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410897692.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-05-09
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

The existing UV sealant has poor high temperature resistance in high temperature environments, and it is difficult to coordinate the mechanical properties and high temperature resistance.

Method used

The sealing layer is formed by using modified acrylic esters, epoxy resins, reactive diluents and reinforcement fillers (alumina powder, silicone powder and LDH) in combination, and a photoinitiator is added to form a sealing layer by ultraviolet light curing.

Benefits of technology

It achieves good mechanical properties and sealing properties that are still maintained in high temperature environments, can withstand high temperatures of 265°C, and has no by-products in the curing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004929527410000101
    Figure BDA0004929527410000101
  • Figure BDA0004929527410000111
    Figure BDA0004929527410000111
Patent Text Reader

Abstract

The invention discloses an environmentally friendly UV sealant, which comprises the following components, measured in parts by weight: 40-80 parts of modified acrylate, 10-20 parts of epoxy resin, 20-40 parts of active diluent, 1-10 parts of reinforcing filler and 0.5-5 parts of photoinitiator; the reinforcing filler is a composite filler, and the composite filler comprises alumina powder, silica gel powder and LDH in a mass ratio of (1-2):(1-3):(0.5-1); the UV sealant can be quickly cured and formed, has no by-products during the curing process, has good moisture resistance, and has excellent mechanical properties of the colloid after curing, good moisture resistance, high hardness, and still maintains good mechanical properties at high temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to an environmentally friendly sealing UV adhesive and a preparation method thereof. Background Art

[0002] UV glue is widely used in the fields of glass products, medical equipment, electronics, electrical appliances, optoelectronics, optical instruments, etc., such as the manufacture of electronic circuit boards, electronic components, digital cameras, electronic scales, buzzer chips and other products. The curing principle of UV glue is that the photoinitiator (or photosensitizer) in the UV curing material absorbs ultraviolet light under ultraviolet light, produces active free radicals or cations, and initiates monomer polymerization, cross-linking and branching chemical reactions. Therefore, the adhesive can be transformed from liquid to solid within a few seconds, and has the characteristics of fast curing speed, controllable reaction, solvent-free, and pollution-free. However, the existing UV sealants generally have poor high temperature resistance. They are prone to lose their sealing effect when used in high temperature environments for a long time, which has an adverse effect on the product, and the mechanical properties and high temperature resistance cannot be coordinated.

[0003] CN118006268A discloses a blue light band photocuring epoxy sealant and a preparation method thereof. 30 to 80 parts by weight of alicyclic epoxy resin, 30 to 60 parts by weight of epoxy oligomer silicone resin, 0.1 to 3 parts by weight of defoamer, 1 to 5 parts by weight of fumed silica, 0.1 to 5 parts by weight of silane coupling agent and 1 to 10 parts by weight of cationic photoinitiator are reacted to obtain a blue light band photocuring epoxy sealant having high flexibility, high toughness and good adhesion properties. However, the main purpose of the patent is to improve the flexibility and toughness of the sealant, and the high temperature resistance level is not disclosed.

[0004] CN114032036B discloses a high temperature resistant UV curing sealant and a preparation method thereof, which is composed of modified acrylate, hydrocarbon resin, acrylic monomer, photoinitiator, reinforcing filler and auxiliary agent. The modified acrylate used is linear acrylate and its derivatives, and the linear main chain of linear acrylate and its derivatives has a polybutadiene structure. The hydrocarbon resin used is a linear carbon main chain and contains a benzene ring structure in the side chain. The sealant can withstand high temperatures such as reflow soldering temperature; the sealant mainly has a linear chain structure and good flexibility, but average strength and hardness.

[0005] Therefore, it is necessary to develop light-curing sealants that maintain good mechanical properties at high temperatures. Summary of the invention

[0006] In view of the above problems, the purpose of the present invention is to provide an environmentally friendly sealing UV glue and a preparation method thereof, wherein the sealing UV glue not only has good moisture resistance but also excellent mechanical properties, and still has good mechanical properties and sealing properties under high temperature environment.

[0007] To this end, the present invention adopts the following technical solutions:

[0008] The invention provides an environmentally friendly UV sealing adhesive, which comprises the following components, measured in parts by weight: 40-80 parts of modified acrylate, 10-20 parts of epoxy resin, 20-40 parts of active diluent, 1-10 parts of reinforcing filler and 0.5-5 parts of photoinitiator; the reinforcing filler is a composite filler, and the composite filler comprises alumina powder, silica gel powder and LDH in a mass ratio of (1-2):(1-3):(0.5-1).

[0009] Furthermore, the preparation method of the modified acrylate comprises the following steps:

[0010] S1, adding isobutyl acrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl acrylate and 2 / 3 of the initiator azobisisobutyronitrile in a mass ratio of (1-3):(1-3):(1-2):(0.5-1.5) into a reaction container, and stirring to mix evenly;

[0011] S2, add isopropanol, raise the temperature to 30-40°C, then dropwise add 3-(2,3-epoxypropoxy)propyltriethoxysilane and vinyltrimethoxysilane in a mass ratio of (1-3):1, and evenly add the dropwise addition within 30-40 minutes, then raise the temperature to 80-85°C, stir and react at a constant temperature for 0.5-2 hours, then add the remaining 1 / 3 of the initiator azobisisobutyronitrile, and continue to stir and react at a constant temperature for 1-3 hours;

[0012] S3, after the reaction is finished, the temperature is lowered to 35°C to stop the reaction, and the product is collected after separation and purification.

[0013] Preferably, the sum of the weights of the 3-(2,3-epoxypropoxy)propyltriethoxysilane and vinyltrimethoxysilane accounts for 0.5-5% of the sum of the weights of isobutyl acrylate, isobornyl methacrylate, lauryl methacrylate and 2-hydroxyethyl acrylate.

[0014] Preferably, the epoxy resin is bisphenol A glycidyl ether epoxy resin.

[0015] Preferably, the reactive diluent is selected from at least one of isooctyl acrylate, dodecyl methacrylate, isodecyl methacrylate, caprolactone methacrylate, ethylene glycol diacrylate, hexanediol diacrylate and tripropylene glycol diacrylate.

[0016] Preferably, the reinforcing filler is a mixture of alumina powder, silica gel powder, talc powder and 2-(3,4-oxirane)ethyltrimethoxysilane in a mass ratio of (1-2):(1-3):(0.5-1):(0.1-1).

[0017] Preferably, the preparation method of the reinforcing filler comprises: dispersing alumina powder, silica gel powder and LDH with a mixed solution of 5-15 times the volume of ethanol and water, adding 2-(3,4-ethylene oxide)ethyltrimethoxysilane, stirring and reacting for 2-5 hours, then concentrating to 1 / 4-1 / 3 of the original volume, grinding and mixing for 10-20 minutes, and drying to obtain the reinforcing filler.

[0018] Preferably, the particle size of the LDH is 5-50 nm.

[0019] Preferably, the photoinitiator is one or more of 1-hydroxycyclohexyl phenyl ketone, benzophenone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate, and ethyl 2,4,6-trimethylbenzoylphenylphosphonate.

[0020] Preferably, the composition further comprises an auxiliary agent, wherein the auxiliary agent is one or more of a defoaming agent, an antioxidant and a pigment.

[0021] The present invention also provides a method for preparing an environmentally friendly sealing UV adhesive, comprising the following steps:

[0022] (1) uniformly mixing the modified acrylate, reactive diluent and photoinitiator;

[0023] (2) adding epoxy resin and reinforcing filler, mixing and grinding, filtering, and obtaining an environmentally friendly sealing UV adhesive.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The environmentally friendly sealing UV glue provided by the present invention is prepared by mixing modified acrylate, epoxy resin, active diluent monomer and reinforcing filler, adding initiator, and the photoinitiator absorbs light energy to rapidly cure and form, and there is no by-product in the curing process. After curing, the colloid has excellent mechanical properties, good moisture resistance, high hardness, can withstand high temperature of 265°C, and still maintains good mechanical properties at high temperature. In the present invention, the modified acrylate, epoxy resin and reinforcing filler can work synergistically to enhance the mechanical properties of the sealant.

[0026] The modified acrylic ester of the invention is prepared by reacting isobutyl acrylate, isobornyl methacrylate, lauryl methacrylate and 2-hydroxyethyl acrylate, and then modified with epoxysilane 3-(2,3-epoxypropoxy)propyltriethoxysilane and vinyltrimethoxysilane to obtain a modified isobutyl acrylate / isobornyl methacrylate / lauryl methacrylate / 2-hydroxyethyl acrylate resin, which has fast UV curing speed and excellent mechanical properties.

[0027] The reinforcing filler of the invention is prepared by mixed reaction of alumina powder, silica gel powder and LDH and modified with epoxysilane 2-(3,4-ethylene oxide)ethyltrimethoxysilane. Compared with conventional fillers, the mechanical properties, hardness and high temperature resistance of the sealant can be better improved.

[0028] In summary, the environmentally friendly sealing UV adhesive of the present invention has excellent comprehensive performance, can fit tightly to sealing devices of different shapes when used, has good sealing performance when used in a high temperature environment, and has broad application prospects. DETAILED DESCRIPTION

[0029] Below by specific embodiment, the specific implementation mode of this explanation technical scheme is further described, these embodiments are for the detailed description of this technical scheme, rather than for limiting this technical scheme. Based on the embodiment in this description, all other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the scope of protection of this description. Unless otherwise specified, the reagent, method and equipment used in the present invention are conventional reagents, methods and equipment in the art, and the reagents and materials used in the following examples are all commercially available.

[0030] Example 1

[0031] The present embodiment provides an environmentally friendly sealing UV glue, which includes the following components, in parts by weight: 60 parts of modified acrylate, 15 parts of bisphenol A glycidyl ether epoxy resin E461A, 20 parts of dodecyl methacrylate, 6 parts of hexanediol diacrylate, 6 parts of reinforcing filler, 1.5 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 1 part of benzophenone.

[0032] The preparation method of the modified acrylate comprises the following steps:

[0033] S1, adding isobutyl acrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl acrylate and 2 / 3 of the initiator azobisisobutyronitrile in a mass ratio of 1.5:3:1:1 into a reaction container, and stirring to mix evenly;

[0034] S2, add isopropanol, raise the temperature to 40°C, then drop 3-(2,3-epoxypropoxy)propyltriethoxysilane and vinyltrimethoxysilane in a mass ratio of 3:1, and evenly add the dropwise addition within 30 minutes, then raise the temperature to 85°C, stir and react at a constant temperature for 1.5 hours, then add the remaining 1 / 3 of the initiator azobisisobutyronitrile, and continue to stir and react at a constant temperature for 3 hours;

[0035] S3, after the reaction is finished, the temperature is lowered to 35°C to stop the reaction, and the product is collected after separation and purification.

[0036] The reinforcing filler is a mixture of alumina powder, silica gel powder, LDH and 2-(3,4-ethylene oxide)ethyltrimethoxysilane in a mass ratio of 1:1.5:1:0.23, and the preparation method is: disperse the alumina powder, silica gel powder and LDH in a mixed solution of ethanol and water, add 2-(3,4-ethylene oxide)ethyltrimethoxysilane in an amount of 5wt% of the total weight of the filler, stir and react for 4h, then concentrate to 1 / 4 of the original volume, grind and mix for 15min, and dry to obtain the reinforcing filler.

[0037] The preparation method of the environmentally friendly sealing UV adhesive of this embodiment comprises the following steps:

[0038] (1) uniformly mixing modified acrylate, dodecyl methacrylate, hexanediol diacrylate, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and benzophenone;

[0039] (2) adding epoxy resin and reinforcing filler, mixing and grinding, filtering, and obtaining an environmentally friendly sealing UV adhesive.

[0040] Preparation Example 2

[0041] The present embodiment provides an environmentally friendly sealing UV glue, which includes the following components, in parts by weight: 70 parts of modified acrylate, 20 parts of bisphenol A glycidyl ether epoxy resin E461A, 20 parts of dodecyl methacrylate, 15 parts of hexanediol diacrylate, 10 parts of reinforcing filler, 1.5 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 1 part of benzophenone.

[0042] The preparation method of the modified acrylate comprises the following steps:

[0043] S1, adding isobutyl acrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl acrylate and 2 / 3 of the initiator azobisisobutyronitrile in a mass ratio of 2:3:1:1 into a reaction container, and stirring to mix evenly;

[0044] S2, add isopropanol, raise the temperature to 40°C, then drop 3-(2,3-epoxypropoxy)propyltriethoxysilane and vinyltrimethoxysilane in a mass ratio of 3:1, and evenly add the dropwise addition within 30 minutes, then raise the temperature to 85°C, stir and react at a constant temperature for 1 hour, then add the remaining 1 / 3 of the initiator azobisisobutyronitrile, and continue to stir and react at a constant temperature for 3 hours;

[0045] S3, after the reaction is finished, the temperature is lowered to 35°C to stop the reaction, and the product is collected after separation and purification.

[0046] The reinforcing filler is a mixture of alumina powder, silica gel powder, LDH and 2-(3,4-ethylene oxide)ethyltrimethoxysilane in a mass ratio of 1:1:1:0.2, and the preparation method is: disperse the alumina powder, silica gel powder and LDH with a mixed solution of ethanol and water, add 2-(3,4-ethylene oxide)ethyltrimethoxysilane in an amount of 5wt% of the total weight of the filler, stir and react for 4h, then concentrate to 1 / 4 of the original volume, grind and mix for 15min, and dry to obtain the reinforcing filler.

[0047] The preparation method of the environmentally friendly sealing UV adhesive of this embodiment comprises the following steps:

[0048] (1) uniformly mixing modified acrylate, dodecyl methacrylate, hexanediol diacrylate, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and benzophenone;

[0049] (2) adding epoxy resin and reinforcing filler, mixing and grinding, filtering, and obtaining an environmentally friendly sealing UV adhesive.

[0050] Example 3

[0051] The present embodiment provides an environmentally friendly sealing UV adhesive, which includes the following components, in parts by weight: 45 parts of modified acrylate, 10 parts of bisphenol A type glycidyl ether epoxy resin E461A, 30 parts of active diluent, 3 parts of reinforcing filler, 1 part of ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 1 part of benzophenone.

[0052] The preparation method of the modified acrylate comprises the following steps:

[0053] S1, adding isobutyl acrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl acrylate and 2 / 3 of the initiator azobisisobutyronitrile in a mass ratio of 1:1:1:0.5 into a reaction container, and stirring and mixing evenly;

[0054] S2, add isopropanol, raise the temperature to 40°C, then drop 3-(2,3-epoxypropoxy)propyltriethoxysilane and vinyltrimethoxysilane in a mass ratio of 3:1, and evenly add the dropwise addition within 30 minutes, then raise the temperature to 85°C, stir and react at a constant temperature for 1 hour, then add the remaining 1 / 3 of the initiator azobisisobutyronitrile, and continue to stir and react at a constant temperature for 3 hours;

[0055] S3, after the reaction is finished, the temperature is lowered to 35°C to stop the reaction, and the product is collected after separation and purification.

[0056] The reinforcing filler is a mixture of alumina powder, silica gel powder, LDH and 2-(3,4-ethylene oxide)ethyltrimethoxysilane in a mass ratio of 2:2:0.5:0.3, and the preparation method is: disperse the alumina powder, silica gel powder and LDH in a mixed solution of ethanol and water, add 2-(3,4-ethylene oxide)ethyltrimethoxysilane in an amount of 5wt% of the total weight of the filler, stir and react for 4h, then concentrate to 1 / 4 of the original volume, grind and mix for 15min, and dry to obtain the reinforcing filler.

[0057] The preparation method of the environmentally friendly sealing UV adhesive of this embodiment comprises the following steps:

[0058] (1) uniformly mixing modified acrylate, dodecyl methacrylate, hexanediol diacrylate, ethyl 2,4,6-trimethylbenzoylphenylphosphonate and benzophenone;

[0059] (2) adding epoxy resin and reinforcing filler, mixing and grinding, filtering, and obtaining an environmentally friendly sealing UV adhesive.

[0060] Comparative Example 1

[0061] This comparative example provides a sealing UV glue, which is different from Example 1 in that the modified acrylic resin is replaced by an equal weight portion of thermoplastic acrylic resin (model 518, purchased from Hanpin Paint (Shandong) Co., Ltd.), and the rest is the same as the example.

[0062] The preparation method of the sealing UV glue in this comparative example is the same as that in Example 1.

[0063] Comparative Example 2

[0064] This comparative example provides a sealing UV glue, which is different from Example 1 in that the modified acrylic resin is replaced by an acrylic resin of equal weight, and the other parts are the same.

[0065] The acrylic resin is different from the modified acrylic resin in that the acrylic resin is not modified by using 3-(2,3-epoxypropoxy)propyltriethoxysilane and vinyltrimethoxysilane.

[0066] The specific preparation method is as follows: (1) adding isobutyl acrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl acrylate and initiator azobisisobutyronitrile in a mass ratio of (1-3):(1-3):(1-2):(0.5-1.5) into a reaction vessel, and stirring and mixing evenly for 1-5 hours; (2) cooling to 35°C after the reaction is completed to stop the reaction, and collecting the product after separation and purification.

[0067] The preparation method of the sealing UV glue in this comparative example is the same as that in Example 1.

[0068] Comparative Example 3

[0069] This comparative example provides a sealing UV adhesive, which is different from Example 1 in that bisphenol A glycidyl ether epoxy resin is not added, and the other aspects are the same.

[0070] The preparation method of the sealing UV glue in this comparative example is the same as that in Example 1.

[0071] Comparative Example 4

[0072] This comparative example provides a sealing UV adhesive, which is different from Example 1 in that no reinforcing filler is added, and the other aspects are the same.

[0073] The preparation method of the sealing UV glue in this comparative example is the same as that in Example 1.

[0074] Comparative Example 5

[0075] This comparative example provides a sealing UV adhesive, which is different from Example 1 in that the reinforcing filler is replaced with an equal weight portion of fumed silica, and the other parts are the same.

[0076] The preparation method of the sealing UV glue in this comparative example is the same as that in Example 1.

[0077] Comparative Example 6

[0078] This comparative example provides a sealing UV glue, which is different from Example 1 in that the reinforcing filler is replaced by 2 parts by weight of alumina powder, 2 parts by weight of silica gel powder, and 2 parts by weight of LDH, and the three components are added separately, and the others are the same.

[0079] The preparation method of the sealing UV glue in this comparative example is the same as that in Example 1.

[0080] Comparative Example 7

[0081] This comparative example provides a sealing UV adhesive, which is different from Example 1 in that the reinforcing filler is replaced with an equal weight portion of aluminum oxide powder, and the other parts are the same.

[0082] The preparation method of the sealing UV glue in this comparative example is the same as that in Example 1.

[0083] Comparative Example 8

[0084] This comparative example provides a sealing UV glue, which is different from Example 1 in that the reinforcing filler is replaced by silica gel powder in equal parts by weight, and the other parts are the same.

[0085] The preparation method of the sealing UV glue in this comparative example is the same as that in Example 1.

[0086] Comparative Example 9

[0087] This comparative example provides a sealing UV adhesive, which is different from Example 1 in that the reinforcing filler is replaced by LDH in equal parts by weight, and the other parts are the same.

[0088] The preparation method of the sealing UV glue in this comparative example is the same as that in Example 1.

[0089] Performance Test:

[0090] The following performance tests were performed on the sealing UV adhesives prepared in the above Examples 1-3 and Comparative Examples 1-9.

[0091] 1. Test method for tensile strength: refer to GB / T 7124-2008;

[0092] 2. Test method for elongation at break: refer to GB-T1040-1992;

[0093] 3. Shear strength test method: refer to GB / T 7124-2008;

[0094] 4. Water vapor transmission rate: The water vapor transmission rate was measured using a water permeability meter (Model 3, MOCON) at 40°C and 100% relative humidity for 24 h.

[0095] The test results are shown in Table 1.

[0096] Table 1 Performance test results

[0097]

[0098]

[0099] As can be seen from Table 1, the UV glue provided by Examples 1-3 of the present invention has a fast curing speed and can be completely cured in 8-12 seconds. The tensile strength at room temperature can reach 24.3 MPa, and the tensile strength at 260°C can still reach 21.7 MPa. The elongation at break can reach 471.2, the hardness can reach 83HA, and the water vapor permeability can be as low as 0.59 g / m 2 ·24h, indicating that the environmentally friendly sealing UV adhesive provided by the present invention has good mechanical properties, high temperature resistance and moisture resistance, and good sealing performance.

[0100] Compared with Example 1, the difference of Comparative Example 1 is that the modified acrylic resin is replaced by an equal weight portion of thermoplastic acrylic resin. The tensile strength of the prepared sealant at room temperature decreases, the tensile strength at 260°C also decreases significantly, the hardness also decreases significantly, the water vapor permeability is significantly improved, and the curing time is longer, indicating that the modified acrylic resin of the present invention cures faster than conventional thermoplastic acrylates, and can better improve the mechanical properties, moisture resistance and high temperature resistance of the sealant.

[0101] Compared with Example 1, the difference of Comparative Example 2 is that the modified acrylic resin is replaced with an acrylic resin of equal weight, and the acrylic resin is not modified with 3-(2,3-epoxypropoxy)propyltriethoxysilane and vinyltrimethoxysilane. The tensile strength of the prepared sealant at room temperature decreases, the tensile strength at 260°C also decreases significantly, the hardness also decreases significantly, the water vapor permeability increases significantly, and the moisture resistance decreases; the performance of the sealant in Comparative Example 2 is better than that in Comparative Example 1, indicating that the modified acrylic resin of the present invention can better improve the mechanical properties, moisture resistance and high temperature resistance of the sealant.

[0102] Compared with Example 1, the difference of Comparative Example 3 is that bisphenol A glycidyl ether epoxy resin is not added. The tensile strength of the prepared sealant at room temperature decreases, the tensile strength at 260°C also decreases significantly, the hardness also decreases significantly, the water vapor permeability increases significantly, and the moisture resistance decreases, indicating that the modified acrylic resin and bisphenol A glycidyl ether epoxy resin used in the sealant formula of the present invention can coordinately improve the mechanical properties, moisture resistance and high temperature resistance of the sealant.

[0103] Compared with Example 1, the difference of Comparative Example 4 is that no reinforcing filler is added. The tensile strength of the prepared sealant at room temperature decreases, the tensile strength at 260°C also decreases significantly, the hardness also decreases significantly, the water vapor permeability increases significantly, the moisture resistance decreases, and the performance decrease of Comparative Example 4 is greater than that of Comparative Examples 1-3. It shows that the reinforcing filler in the sealant formula of the present invention is matched with the modified acrylic resin, bisphenol A type glycidyl ether epoxy resin and other components to coordinately improve the mechanical properties, moisture resistance and high temperature resistance of the sealant.

[0104] Compared with Example 1, the difference of Comparative Example 5 is that the reinforcing filler is replaced with an equal weight portion of fumed silica. The tensile strength of the prepared sealant at room temperature decreases, the tensile strength at 260°C also decreases significantly, the hardness also decreases significantly, the water vapor permeability increases significantly, and the moisture resistance decreases. It shows that the reinforcing filler provided by the present invention can better improve the mechanical properties, moisture resistance and high temperature resistance of the sealant than the fumed silica filler.

[0105] Compared with Example 1, the difference of Comparative Example 6 is that the reinforcing filler is replaced by 2 parts by weight of alumina powder, 2 parts by weight of silica gel powder and 2 parts by weight of LDH. The tensile strength of the prepared sealant at room temperature decreases, the tensile strength at 260°C also decreases significantly, the hardness also decreases significantly, the water vapor permeability increases significantly, and the moisture resistance decreases. It shows that the reinforcing filler provided by the present invention can better improve the mechanical properties, moisture resistance and high temperature resistance of the sealant.

[0106] Compared with Example 1, the difference between Comparative Examples 7-9 is that the reinforcing fillers are replaced with equal weight portions of alumina powder, silica gel powder or LDH. The tensile strength of the prepared sealant at room temperature decreases, the tensile strength at 260°C also decreases significantly, the hardness also decreases significantly, the water vapor permeability increases significantly, and the moisture resistance decreases. This shows that the reinforcing filler provided by the present invention can better improve the mechanical properties, moisture resistance and high temperature resistance of the sealant than the single component alumina powder, silica gel powder or LDH.

[0107] In summary, the environmentally friendly sealing UV adhesive of the present invention has a fast curing speed, good mechanical properties, high temperature resistance and moisture resistance, and good sealing performance.

[0108] Although the embodiments of the present description have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present description, the scope of which is defined by the appended claims and their equivalents.

Claims

1. An environmentally friendly sealing UV adhesive, characterized in that: The invention comprises the following components in parts by weight: 40-80 parts of modified acrylate, 10-20 parts of epoxy resin, 20-40 parts of active diluent, 1-10 parts of reinforcing filler and 0.5-5 parts of photoinitiator; the reinforcing filler is a composite filler, and the composite filler comprises alumina powder, silica gel powder and LDH in a mass ratio of (1-2):(1-3):(0.5-1); the preparation method of the modified acrylate comprises the following steps: S1, treating the epoxy resin and the photoinitiator in a mass ratio of (1-3):(0.5-1); ):(1-3):(1-2):(0.5-1.5) of isobutyl acrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl acrylate and 2 / 3 of the initiator azobisisobutyronitrile are added to the reaction vessel and stirred to mix evenly; S2, isopropanol is added, the temperature is raised to 30-40°C, and then 3-(2,3-epoxypropoxy)propyltriethoxysilane and vinyltrimethoxysilane are added dropwise at a mass ratio of (1-3):1 at 30-40°C. min, then the temperature is raised to 80-85°C, and the reaction is stirred at a constant temperature for 0.5-2h, and then the remaining 1 / 3 of the initiator azobisisobutyronitrile is added, and the reaction is continued at a constant temperature for 1-3h; S3, the reaction is completed and the temperature is lowered to 35°C, the reaction is stopped, and the product is collected after separation and purification; the epoxy resin is bisphenol A type glycidyl ether epoxy resin; the sum of the weight of the 3-(2,3-epoxypropoxy)propyltriethoxysilane and vinyltrimethoxysilane accounts for 1.3% of the acrylic acid 0.5-5% of the sum of the weight of isobutyl ester, isobornyl methacrylate, lauryl methacrylate and 2-hydroxyethyl acrylate; the preparation method of the reinforcing filler comprises: dispersing alumina powder, silica gel powder and LDH with a mixed solution of 5-15 times the volume of ethanol and water, adding 2-(3,4-ethylene oxide)ethyltrimethoxysilane, stirring and reacting for 2-5 hours, then concentrating to 1 / 4-1 / 3 of the original volume, grinding and mixing for 10-20 minutes, and drying to obtain the reinforcing filler.

2. The environmentally friendly sealing UV adhesive according to claim 1, characterized in that: The active diluent is selected from at least one of isooctyl acrylate, dodecyl methacrylate, isodecyl methacrylate, caprolactone methacrylate, ethylene glycol diacrylate, hexanediol diacrylate and tripropylene glycol diacrylate.

3. The environmentally friendly sealing UV adhesive according to claim 1, characterized in that: The particle size of the LDH is 5-50 nm.

4. The environmentally friendly sealing UV adhesive according to claim 1, characterized in that: The photoinitiator is one or more of 1-hydroxycyclohexyl phenyl ketone, benzophenone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate, and 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester.

5. The environmentally friendly sealing UV adhesive according to claim 1, characterized in that: The invention also comprises auxiliary agents, which are one or more of defoaming agents, antioxidants and pigments.

6. The method for preparing the environmentally friendly sealing UV adhesive according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Mixing the modified acrylate, reactive diluent and photoinitiator uniformly; (2) Add epoxy resin and reinforcing filler, mix and grind, and filter to obtain environmentally friendly sealing UV glue.

Citation Information

Patent Citations

  • Preparation method of UV curable urethane acrylate adhesive

    CN109796917A

  • High-temperature-resistant UV curing sealant and preparation method thereof

    CN114032036A